"Ghost Introgression" As a Cause of Deep Mitochondrial Divergence in a Bird Species Complex. (27th July 2019) - Zhang, Dezhi; Tang, Linfang; Cheng, Yalin; Hao, Yan; Xiong, Ying; Song, Gang; Qu, Yanhua; Rheindt, Frank E; Alström, Per; Jia, Chenxi; Lei, Fumin
Abstract: In the absence of nuclear-genomic differentiation between two populations, deep mitochondrial divergence (DMD) is a form of mito-nuclear discordance. Such instances of DMD are rare and might variably be explained by unusual cases of female-linked selection, by male-biased dispersal, by "speciation reversal" or by mitochondrial capture through genetic introgression. Here, we analyze DMD in an Asian Phylloscopus leaf warbler (Aves: Phylloscopidae) complex. Bioacoustic, morphological, and genomic data demonstrate close similarity between the taxa affinis and occisinensis, even though DMD previously led to their classification as two distinct species. Using population genomic and comparative genomic methods on 45 whole genomes, including historical reconstructions of effective population size, genomic peaks of differentiation and genomic linkage, we infer that the form affinis is likely the product of a westward expansion in which it replaced a now-extinct congener that was the donor of its mtDNA and small portions of its nuclear genome. This study provides strong evidence of "ghost introgression" as the cause of DMD, and we suggest that "ghost introgression" may be a widely overlooked phenomenon in nature.